(3GdeaGgje GdYdejI hGdJWHjbGJ GdEOGQjI (B-(3GdLRA GdChd(B-s - (3GMeO eMeO(B, (3Zfjes ((3GdbGgQI(B:s (3GdecJHI GdYUQjI(B,s, 2007)
(3jMJhj gPG GdcJGH Ydi(B:(3fXQjI GdbQGQ,GdHQeLI GdNWjI, JMdjd GdMSGSjI,GSdhH Gdfbd, fehPL GdJNUjU,HQeLI GdCgOGa, GdHQeLI ZjQ GdNWjI, GdHQeLI GdEMJeGdjI, GdHQeLI HGdCYOGO GdUMjMI,GdHQeLI GdHGQGeJQjI, GdHQeLI GdOjfGejcjI, CSdhH JMdjd GdeONdGJ h GdeNQLGJ, CSdhH eGQcha, feGPL THcGJ GdCYeGd,CSdhHj Jbjje h eQGLYI GdHQGeL h GdeSGQ GdMQL, CSdhH JMdjd GdefGaY h GdJcGdja,fXQjI GdeHGQjGJ,fXQjI Uaha GdEfJXGQ, CSdhH GdeMGcGI(B.s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdHQeLIs; (3GdHQeLI GdNWjIs